ANALISIS PERPUTARAN PERSEDIAAN BARANG JADI UNTUK MENINGKATKAN EFEKTIFITAS DAN EFISIENSI PRODUKSI PADA PT XYZ - Safri Safri (JURNAL MITRA MANAJEMEN, 2020)
ABSTRACTInventories must always be in optimal condition, optimal in the sense that there are not many and also not small, excess inventory of finished goods results in increased storage burden and may be expired, while shortages result in companies losing sales. PT XYZ is a company engaged in cardboard box manufacturing. From the company's data processing, it is obtained that the analysis of the average inventory turnover of finished goods with PT XYZ standards during 2016 is still below the company standard, which is 2 times a month. The results of the analysis of the average inventory turnover of finished goods with PT XYZ standards during 2016 are above the company standard, which is 15 days a month. The company should accelerate the time of the inventory turnover period, by increasing sales performance so that it does not cause a buildup of goods which results in additional costs and decreased quality of finished goods inventory. Keywords: effective and efficiency, Finished Goods, Inventory Turnover